AI and Global Marketing in the Digital Age - Ngamvichaikit, Anothai (Modern Management Frontier Journal, 2025)
This article presents an overview of the application of Artificial Intelligence (AI) in global marketing in the digital age. Currently, business organizations are increasingly adopting AI technologies to enhance their global marketing strategies, necessitating an understanding of the impacts, challenges, and opportunities arising from such utilization. This paper examines the impact of AI on various aspects of global marketing strategies, drawing on empirical research and practical insights, covering issues of market forecasting, consumer behavior analysis, and cross-cultural communication. It also reviews AI-enhanced global marketing strategies such as data-driven consumer behavior analysis, culturally aware marketing, language localization, hyper-personalization, and predictive analytics. The article addresses the challenges in integrating AI in global marketing, including ethical considerations, cultural sensitivity, technological disparities, and regulatory compliance. It presents case studies of global brands like Netflix, Unilever, and Alibaba to illustrate successful AI integration in global marketing scenarios. Finally, the paper points out future directions for AI in global marketing, emphasizing the necessity for continuous learning, adaptation, and ethical considerations.